The Teaching Style of English Teachers in Maintaining Students’ Motivation in Learning English at SMA Negeri 1 Enrekang - Umiyati Jabri (Majesty Journal, 2019)
This study aimed to identify the teaching styles used by English teachers at SMA Negeri 1 Enrekang, to determine the teaching styles preferred by second-grade students, and to examine whether the teachers’ teaching styles could maintain students’ motivation in learning English. The study employed a descriptive design. The participants were two English teachers and 30 second-grade students selected from two classes. Data were collected through an observation checklist, a questionnaire, and interviews. The findings revealed that the teacher of class XI IPA 3 mainly applied an auditory-oriented teaching style, while the teacher of class XI IPS 1 combined visual and auditory styles. In contrast, students in both classes showed a stronger preference for kinesthetic and visual teaching styles. Despite these differences, the students’ motivation toward learning English was categorized as positive in both classes, as indicated by questionnaire results with mean scores of approximately 4.0 on the Likert scale. These findings suggest that teaching style plays an important role in maintaining students’ motivation in English learning. The study concludes that although teachers and students may differ in their preferred teaching styles, appropriate classroom interaction and instructional delivery can still support positive student motivation.